2021
DOI: 10.2147/amep.s300265
|View full text |Cite
|
Sign up to set email alerts
|

Internal Medicine Clerkship Amidst COVID-19 Pandemic: A Cross-Sectional Study of the Clinical Learning Experience of Undergraduate Medical Students at Makerere University, Uganda

Abstract: Background The coronavirus-2019 (COVID-19) pandemic continues to impose a significant impact on medical education. We aimed to describe the clinical learning experience of undergraduate medical students undertaking internal medicine clerkship during the COVID-19 pandemic at Makerere University, Uganda. Methods A descriptive, cross-sectional study among medical students in clinical years of study pursuing the Bachelor of Medicine and Bachelor of Surgery undergraduate deg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…In this unprecedented era, e-learning may be an ideal option ( 3 ). However, it seems more applicable to preclinical phases of medical education, which are lecture-based.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this unprecedented era, e-learning may be an ideal option ( 3 ). However, it seems more applicable to preclinical phases of medical education, which are lecture-based.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, clinical stages of medical education oblige students to work in interdisciplinary teams to practice their newly acquired clinical abilities while learning about the healthcare system. Therefore, the shift to e-learning may not facilitate clinical skills and competency acquisition during this stage ( 3 , 4 ). However, it is understandable that medical schools had to postpone clinical clerkships to reduce student exposure, flatten the curve, and protect healthcare workers during the pandemic due to a lack of personal protective equipment (PPE) ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Looking back, emerging pandemics such as Severe Acute Respiratory Syndrome (SARS) [ 9 – 11 ], the 2009 H1N1 influenza [ 12 ], and the Middle East Respiratory Syndrome [ 13 ] have significantly impacted medical students. The negative effects of the COVID-19 pandemic on medical education have also been reported in various fields such as surgical training [ 14 ], pre-clerkship, and clerkship learning [ 15 , 16 ], A survey on medical students in the United States suggested that about one-fifth of the respondents considered that the COVID-19 pandemic would unfavourably influence their choices of professional specialty [ 17 ]. Another report revealed that career choices for being good physicians markedly increased among two-thirds of students, although they focused on paediatric fields [ 18 ]; however, to the best of our knowledge, no survey has specifically investigated medical students’ career choices toward becoming ID specialists during an emerging pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the location, the impact of COVID-19 continues to vary widely among AAMC-member medical schools with geographic containment seen but also simultaneous outbreaks and surges in cases across the country and the world where regions in south-east Asia and South America are being disproportionately affected during this spring resurgence. Medical students across the world have been placed in a challenging situation where the disruption of valuable clinical education adds to the sense of inadequate preparedness as future healthcare providers [ 23 – 25 ]. Telemedicine has been increasingly adopted during the pandemic and will likely have a permanent place in the future of healthcare [ 26 ].…”
Section: Discussionmentioning
confidence: 99%